Implementasi Penyuluhan Tanah Wakaf dalam Rangka Menghindari Konflik Wakaf Keluarga oleh Badan Wakaf Indonesia (BWI) Kabupaten Pesisir Barat Perspektif Hukum Islam: Studi di Desa Banjar Agung KUA Kecamatan Way Krui Kabupaten Pesisir Barat - Ahmad Dani; Relit Nur Edi; Ahmad Fauzan (Jurnal Hukum Lex Generalis, 2026)
This study was motivated by the low level of public understanding regarding the importance of the administration and legal status of waqf land, which has the potential to cause family waqf disputes. The study aims to examine the implementation of waqf land counseling in preventing family waqf conflicts conducted by the Indonesian Waqf Board (BWI) of West Pesisir Regency from the perspective of Islamic law, as well as to identify the supporting and inhibiting factors. This research employed a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation. The results show that the implementation of waqf land counseling by BWI of West Pesisir Regency in collaboration with the Office of Religious Affairs (KUA) of Way Krui District was carried out through socialization programs, religious gatherings, direct public services, and assistance in waqf administration. The counseling activities had a positive impact on increasing public awareness of the importance of the Waqf Pledge Deed (AIW), waqf land certification, and waqf legality in preventing family conflicts. From the perspective of Islamic law, waqf land counseling is in line with the principle of protecting property (hifz al-mal) within the framework of maqasid al-shariah. Supporting factors include cooperation among BWI, KUA, religious leaders, and village government officials, while inhibiting factors include the low level of public understanding and limited public awareness regarding the importance of waqf land certification.